Compost quality optimization through Plackett-Burman’s design - Luis Felipe Ortiz-Dongo; Yerly Mendez-Revollar; Richard Solórzano-Acosta; Sphyros Lastra; Gladys Carrión-Carrera (International Journal of Recycling of Organic Waste in Agriculture)
Purpose: This research aimed at compost quality optimization through Plackett-Burman’s design application. This statistical method was used to identify and evaluate key factors that impact compost quality and determine its optimal levels.